Transactional Leadership Patterns For Human Resources Development : Pola Kepemimpinan Transaksional Kepala Madrasah Untuk Pengembangan Sumber Daya Alam Manusia - Ahmad Bukron; Budi Haryanto (Academia Open, 2021)
The pattern of leadership is a style or model of leadership used by leaders to influence subordinates so that organizational goals are achieved or it can also be said that leadership style is a pattern of behavior and strategies that are preferred and often applied by a leader. A leader in an educational institution must have a style or model in order to influence his subordinates in order to achieve goals at the institution. The transactional leadership pattern can be interpreted as the method used by a leader in moving his members by offering rewards/consequences for each contribution made by members to the organization. The focus of this research is to find out the leadership pattern of a madrasah principal in his efforts to develop human resources, in this case educators and education staff. Because in reality, madrasas are still seen as educational institutions that are less good than public schools. The progress of an educational institution cannot be separated from the participation of the principal, educators, teaching staff and parents of students. The author sees the leadership pattern of the head of MI Muhammadiyah 2 Kedungbanteng Tanggulangin with a transactional leadership pattern This study uses a descriptive method which is carried out through data collection in the field, which provides an overview of the leadership of the madrasah principal. This research approach uses a qualitative approach. The data of this research are in the form of quotes, words, phrases, and story sentences. From the research conducted, MI Muhammadiyah 2 Kedungbanteng has not yet fully implemented the pattern of transactional leadership, because the exiting human resources tend to stagnate and do not develop in terms of academic graduates who are generally reluctant tot continue their studie at a higher level.